Determination of Apolipoprotein(a) Isoforms and Lipoprotein(a) in Children with Diabetes Mellitus Type 1 - Katerina Tosheska; Danica Labudovic; Sonja Alabakovska; Mirko Spiroski; Bojana Todorova (Turkish Society of Biochemistry, 2007)
Lipoprotein(a) is composed of apoB–100 and the unique protein apolipoprotein(a). Plasma levels of Lipoprotein(a) are determined largely by variation in the gene that encodes it. High plasma levels and small-sized apolipoprotein(a) isoforms are thought to be an independent risk factor for development of atherosclerosis. Children with diabetes mellitus are prone to early development of atherosclerosis. We investigated apolipoprotein(a) polymorphisms and lipoprotein(a) plasma concentrations in 60 normoalbuminuric children with diabetes mellitus type 1 and in 100 healthy children aged between 9 and 17 years. Sodium dodecyl sulphate polyacrylamide gel electrophoresis was used for separation of apolipoprotein(a) isoforms. Individuals expressed a single band (homozygotic), a double band (heterozygotic) or no band (null phenotype). In both groups single-banded phenotypes were more common than double-banded phenotypes: 50.0 % vs. 46.7 % for patients and 53.0 % vs. 43.0 % for controls. A higher prevalence of large size (≥22 Kringle IV repeats) apolipoprotein(a) isoforms, associated with lower lipoprotein(a) concentrations, was detected in the patients and in the controls. Most plasma lipoprotein(a) levels were in the low range. Lipoprotein(a) concentrations below the risk limit of 30 mg/dL were present in 90 % of subjects. The comparison of the two groups showed no significant difference between their mean and median plasma concentration of lipoprotein(a).
Tip 1 Diyabetli Çocuklarda Apolipoprotein(a) İsoformları ve Lipoprotein(a) Tayini
Keywords: apolipoprotein(a); children; diabetes mellitus; lipoprotein(a); sodium dodecyl sulphate polyacrylamide gel electrophoresis